AN INTRODUCTION TO SAN VICENTE (CHICHONTEPEC) VOLCANO, EL SALVADOR - Rotolo, S. G. (2011)
San Vicente is a composite volcano whose oldest volcanic events (2.2 Ma) are recorded in the westernsector, where the remnants of the older La Carbonera edifice outcrop. This volcanic center, which produced mildlytholeiitic to transitional lavas, collapsed during a plinian eruption, giving rise to the formation of a partially preservedcaldera (La Carbonera caldera). The renewal of volcanic activity started with clearly calc-alkaline lavas, mostly two-pyroxene andesites, that built up the San Vicente volcanic edifice. Crystal fractionation had primary control on magmaevolution.The event that triggered the caldera forming plinian eruption is still uncertain; we have some texturalevidences of mixing/mingling with more mafic magmas, but this process seems to be delimited to fewsamples. A major role could have been played by the tectonic instability related to the first stages of centralgraben opening.